ANALISIS MUSIK IRINGAN TARI RADDAT LIHATLAH BULAN DI DESA BEKUT KECAMATAN TEBAS KABUPATEN SAMBAS - Erwin Susanto; Yudhistira Oscar Olendo; Christianly Yeri Silaban (Universitas Tanjungpura, 2021)
Abstract The background of this research is to analyze the structure of the vocal melody and the wasp pattern of tahar raddat, look at the moon. There is a uniqueness in the poetry and wasp pattern of tahar wasps. Both from the textual aspect, namely the musical aspect, as well as from the contextual aspect, namely the aspect of the performing arts. The problem in this research is how the structure of the raddat vocal melody, look at the moon and how the wasp pattern of raddat wasps looks at the moon. The method in this research is descriptive method with qualitative research form. The approach used is the musicology approach. Data collection techniques in this study are observation, interviews, and documentation. This research data collection tool the researcher as the main instrument.This research describes the structure of the vocal melody and describes the wasp pattern of tahar. The surong dayong wasp pattern uses a 4/4 bar, the ngimbai wasp pattern uses a 4/4 bar and the scale used in the vocal melody is the c / natural minor scale and uses the 4/4 rhythm. Tahar has two sound colors, namely the Dung sound color and the Cang sound color. Keywords: Analysis, Raddat take a look at the moon, Vocal, Wasp pattern.